Mycoplasma genitalium compared to chlamydia, gonorrhoea and trichomonas as an aetiological agent of urethritis in men attending STD clinics. Issue 6 (20th April 2009) - Gaydos, C; Maldeis, N E; Hardick, A; Hardick, J; Quinn, T C
Abstract : Objectives: To investigate prevalence of Mycoplasma genitalium, Chlamydia trachomatis, Neisseria gonorrhoeae and Trichomonas vaginalis in men, frequency of co-infections, and association of organisms with urethritis in men. Methods: This was a cross-sectional study of 290 men (age range 19–34 years) attending Baltimore City STD clinics. M genitalium, C trachomatis, N gonorrhoeae and T vaginalis, during 2004 were detected using nucleic acid amplification tests (NAATs) (153 with urethritis and 137 without urethritis). Demographic characteristics and risk factors were ascertained. Results: The overall prevalences of infection with C trachomatis, N gonorrhoeae, T vaginalis and M genitalium were 20.3%, 12.8%, 3.4% and 15.2%, respectively. Prevalences in men with urethritis were 32.7%, 24.2%, 5.2% and 22.2% for C trachomatis, N gonorrhoeae, T vaginalis and M genitalium, respectively. Percentages of co-infections were high. All men with N gonorrhoeae had urethritis. C trachomatis and M genitalium were found to be significantly associated with urethritis in univariate analysis and in multiple logistic regression analysis. Conclusion: The association of M genitalium with urethritis in this study provides confirmation of the importance of screening men for M genitalium as a cause of non-gonococcal urethritis and supports treatment considerations for urethritis for agents other than gonococci and chlamydia.